1991
DOI: 10.1007/bf01233626
|View full text |Cite
|
Sign up to set email alerts
|

The gonadotropin-releasing hormone (Gnrh) gene maps to mouse chromosome 14 and identifies a homologous region on human chromosome 8

Abstract: The murine gonadotropin-releasing hormone (Gnrh) locus has been mapped to mouse chromosome 14 using a mouse x Chinese hamster somatic cell hybrid panel. The equivalent human locus, known as luteinizing hormone-releasing hormone (LHRH), has been previously mapped to 8p21-8p11.2. Four other loci mapping to the human chromosome 8 short arm have been mapped to mouse chromosome 8; two of these (PLAT, GSR) lie proximal to LHRH, and two (LPL, DEF1) lie distal to LHRH. The localization of Gnrh, the murine homolog of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The panel is composed of 26 hybrids having a different subset of mouse chromosomes (Williamson et al 1991). The PCR results indicated that canp3 maps either to mouse Chromosomes (Chrs) 2 or 4 (data not shown), but did not allow distinction between these two chromosomes, since unfortunately all hybrids carrying mouse Chr 2 also carry Chr 4 and vice versa (P. Avner personal communication).…”
Section: Expression and Chromosomal Localization Of The Mouse Muscle-mentioning
confidence: 92%
“…The panel is composed of 26 hybrids having a different subset of mouse chromosomes (Williamson et al 1991). The PCR results indicated that canp3 maps either to mouse Chromosomes (Chrs) 2 or 4 (data not shown), but did not allow distinction between these two chromosomes, since unfortunately all hybrids carrying mouse Chr 2 also carry Chr 4 and vice versa (P. Avner personal communication).…”
Section: Expression and Chromosomal Localization Of The Mouse Muscle-mentioning
confidence: 92%
“…The gene encoding GnRH has been localized to a single locus on chromosome 8 in the human (Yang-Feng et al, 1986) and on chromosome 14 in the mouse (Williamson et al, 1991). Its sequence was originally isolated and identified using a cDNA library derived from human placenta, one of several extrahypothalamic tissues known to synthesize GnRH (Khodr and Siler-Khodr, 1980;Tan and Rousseau, 1982).…”
Section: The Gnrh Genementioning
confidence: 99%
“…BMP2 and 3 map to chromosomes 20 and 4 respectively and arc members of the TGFB family while BMP1 appears to be a regulatory protein. BMP1 maps to human chromosome 8 and to mouse chromosome 14, which together with the reports of Todd et al (Todd et al, 1991) and Williamson et al (Williamson et al, 1991) defines a new man-mouse syntenic group on those two chromosomes.…”
Section: Bmp1mentioning
confidence: 99%